Weight loss as a predictor of mortality in patients with interstitial lung disease. Issue 3 (16th September 2018) - Pugashetti, Janelle; Graham, Julia; Boctor, Noelle; Mendez, Cesar; Foster, Elena; Juarez, Maya; Harper, Richart; Morrissey, Brian; Kadoch, Michael; Oldham, Justin M.
The interstitial lung diseases (ILDs) are a diverse group of diffuse parenchymal lung disorders that commonly result in pulmonary fibrosis. ILDs are broadly classified according to known and unknown aetiologies. Connective tissue disease-associated ILD (CTD-ILD) and chronic hypersensitivity pneumonitis (CHP) are among the most common ILDs of known aetiology, while idiopathic pulmonary fibrosis (IPF) and unclassifiable ILD (U-ILD) are among the most common of unknown aetiology [1–4]. Weight loss in patients with ILD was associated with increased mortality risk in those with IPF and U-ILD http://ow.ly/Nk0D30l2Apm